The Challenges of Islamic Feminism - Ziba Mir-Hosseini (Gender a Výzkum, 2019)
By the early 1990s there were clear signs of the emergence of a new gender discourse that came to be labelled ‘Islamic feminism’. In this paper, I first set this new discourse against the backdrop of the global and local politics of Islam and gender in the latter part of the 20th century. Then I introduce the work of feminist scholar-activists who argue for equality and justice from inside the Muslim tradition, outline how they seek to change the terms of traditional Islamic discourses on gender, and consider their prospects of success. I shall focus on Musawah (www.musawah.org), a global movement for equality and justice in the Muslim family.